Taḥrīk-i taraqqī-yi mumlikat-i Āṣafiyyah : baʻahd-i Maimant Mahad Aʻlāḥaz̤rat Ḥakīmussiyāsat Sult̤ānulʻulūm Āṣif-i Sābiʻ Niẓāmulmulk Navvāb Mīr ʻUs̲mān ʻAlīḵẖāṉ Bahādur bataqrīb-i jashn-i sīmīṉ mubārak vāqiʻ 1346 Fe - Aḥmad, Ḵẖvājah Ḥamīd (SAMP early 20th-century Indian books project ;)
On economic conditions of Hyderabad, India.